Sensibilidad antibiótica en urocultivos de niños de 5 a 11 años del centro de salud Moronacocha Iquitos-Loreto 2022 - Quinteros Saavedra, Antony Javier Efrain (2025)
This study aims to correlate antibiotic sensitivity in urine cultures with sociodemographic and clinical variables (age, sex, self-medication, urinary pathological history, signs, and symptoms) in children aged 5 to 11 years attended at the Moronacocha Health Center in Iquitos, Loreto, in 2022. A quantitative, descriptive, and correlational methodology was used, with a sample of 67 pediatric patients. By analyzing the antibiotic sensitivity results obtained from the urine cultures, the most prevalent bacteria, such as Escherichia coli, Klebsiella sp, and Proteus sp, were identified, as well as their response to common antibiotics such as amikacin, amoxicillin, trimethoprim/sulfamethoxazole, and others. The research found that variables such as sex and self-medication had a significant relationship with antibiotic sensitivity results, while age and prior UTI history showed diverse patterns. It was highlighted that girls were more likely to present urinary infections and greater antibiotic resistance compared to boys. Self-medication also influenced resistance to certain antibiotics, especially in those with a history of UTIs. The results of this study provide valuable information for improving diagnostic and treatment strategies for urinary tract infections in the pediatric population, emphasizing the importance of an integrated approach that considers both biological factors and self medication habits.